Modeling of сoncepts of the New Testament by means of morphology and syntax - Shevchenko, Larysa (Current issues of Ukrainian linguistics: theory and practice, 2018)
The problem of studying text concepts takes an important place among other types of conceptual studies. The usage of the term "concept" in the study of texts is caused by the need for it for the analysis of text-based principles of the work, identification of author’s conceptual priorities, leading themes and ideas, deep text meanings etc. The organization of text’s conceptual associations based on mutually related and interrelated elements goes beyond the lexical-semantic sphere. The conceptosphere of the New Testament is represented not only by lexical means, although they are the main building material for its creation. Morphological and syntactic means have a significant place among the concept-forming elements of the text of the New Testament. The study was conducted through the context-based generalization of the representation units of the most significant concepts of the New Testament: "Jesus Christ", "God", "Lord", "Father", "Faith", "Law", "Sin", "Salvation", "Grace", "Kingdom of Heaven", "Gospel", "Victim". Author had used method of field analysis, which is based on the analysis of the means providing the content order and connectivity of conceptual entities. The basis of systematization in conceptual fields is the linkage of key words – representatives of the morphology and syntax concepts and means. They acquire concept-forming properties when they are used in contexts for the formation of a certain conceptual feature and when they are repeatedly used in the text. The analysis of the verbalizers of the concepts, their connections and interaction in the studied work allows to make conclusions about the basic principles and regularities of the conceptualization of reality in the text of the New Testament. This study of its conceptosphere has demonstrated that the elements of its modeling have a significant representation in the spheres of morphology and syntax. The completeness of the reconstruction of an interpretive picture of its verbalization can be ensured by a comprehensive analysis of their conceptual-forming capabilities.